PREVALENCE OF SENSORINEURAL HEARING LOSS IN TYPE 2 DIABETES MELLITUS PATIENTS AND ITS CORRELATION WITH MICROVASCULAR COMPLICATIONS - THAKURA SOREN,; TANMAINI DAS,; BIBHU PRASAD BEHERA,; MANORANJAN SWAIN,; SARATA CHANDRA SINGH,; MANORANJAN BEHERA, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Studying the prevalence of sensorineural hearing loss in patients with diabetes mellitus (DM) and to find the relationship between the severity of Sensorineural hearing loss (SNHL) with microvascular complications according to age, sexual predominance, duration of disease, and glycemic control (HbA1C) in diabetic patients. Methods: The study population comprised 101 type 2 DM (T2DM) patients as cases, and 101 non-diabetics as controls from the P.G. Department of Medicine, SCB Medical College, Cuttack, from July 2022 to January 2023, and were included in the study after considering the inclusion and exclusion criteria. Results: Among 68 diabetic patients with SNHL, most had a mild degree of 30.7%, followed by a moderate degree of 27.7%, severe and profound being 6.9% and 2%, respectively. Overall, the prevalence of SNHL is 67.3% among cases compared to 21.8% among controls (p<0.001). The proportion of SNHL among diabetes patients with a duration of diabetes of more than 10 years is the highest. The table shows that the proportion of SNHL among diabetes patients with HbA1C between 9.1 and 11 is highest (p=0.025). In our study, as the age of the cases advances, the prevalence of SNHL increases (p=0.013). Conclusion: SNHL is common in T2DM, with a high association with microvascular complications such as diabetic peripheral neuropathy, nephropathy, and retinopathy. As the duration of diabetes and the level of HbA1C progress, the prevalence of hearing loss is found to worsen. Routine audiological evaluation may be carried out to help in the early diagnosis of SNHL.